2017
DOI: 10.1002/hyp.11233
|View full text |Cite
|
Sign up to set email alerts
|

Plant source water apportionment using stable isotopes: A comparison of simple linear, two‐compartment mixing model approaches

Abstract: Plant source water identification using stable isotopes is now a common practice in ecohydrological process investigations. Notwithstanding, little critical evaluation of the approaches for source apportionment have been conducted. Here, we present a critical evaluation of the main methods used for source apportionment between vadose and saturated zone water: simple mass balance and Bayesian mixing models. We leverage new isotope stem water samples from a diverse set of tree species in a strikingly uniform ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 51 publications
(93 reference statements)
8
76
3
Order By: Relevance
“…The general assumption that root water uptake, in most environments, is a nonfractionating process has been shown to be valid in both laboratory (Thorburn et al, ; Wershaw et al, ) and field (White et al, ) settings. Exceptions to this rule, however, have been reported in certain environments (Ellsworth & Williams, ; Evaristo et al, ; Lin & da Sternberg, ). Notwithstanding the long history in the use of water stable isotopes in root water uptake studies, dating back to the seminal work of Dawson and Ehleringer (), its descriptive power in hydrological models is still embryonic.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The general assumption that root water uptake, in most environments, is a nonfractionating process has been shown to be valid in both laboratory (Thorburn et al, ; Wershaw et al, ) and field (White et al, ) settings. Exceptions to this rule, however, have been reported in certain environments (Ellsworth & Williams, ; Evaristo et al, ; Lin & da Sternberg, ). Notwithstanding the long history in the use of water stable isotopes in root water uptake studies, dating back to the seminal work of Dawson and Ehleringer (), its descriptive power in hydrological models is still embryonic.…”
Section: Discussionmentioning
confidence: 94%
“…The stable isotope analysis in R method was an appropriate treatment of our data because of the number of possible sources considered. Evaristo et al () showed that a Bayesian approach constrains the uncertainty estimates better than simple mass balance (e.g., Brunel et al, ) when maximizing the difference between sources is not possible. The use of combined bulk soil water values also leads to more constrained and less diffuse solutions (Phillips et al, ) than if we assigned sources with statistically insignificant differences.…”
Section: Methodsmentioning
confidence: 99%
“…Another explanation for the δ 2 H liq offset between xylem water and probe‐available soil water at Oak site (Figures and ) is that the offset is related to plant water uptake effects. Field studies first showed evidence for H stable isotope discrimination for halophytes and arid xerophytes (Ellsworth & Williams, ; G. Lin & Sternberg, ), and later “uptake effects” were shown to be common in a more diverse set of tree species, many of which were neither halophytes nor xerophytes (Evaristo, McDonnell, & Clemens, ), and have also been shown in lab experiments with Pursea americana (Vargas, Schaffer, Yuhong, & Sternberg, ). Although Q. gambelii is classified as a xerophyte (Abrams, ), its potential for H or O stable isotope discrimination during root water uptake has not been specifically studied.…”
Section: Discussionmentioning
confidence: 95%
“…There appears to be some inconsistency in the hydrogen and oxygen water isotope data, with the hydrogen isotope data showing strong overlap between xylem water and groundwater values, but this is inconsistent for oxygen. The hydrogen isotopic may be a poor tracer of water sources to plants because of its higher energy state and tendency to fractionate (Singer et al, ), with evidence for deuterium fractionation in a wide variety of tree species (Evaristo et al, ). This suggests that the δ 18 O data can be more reliable for water source tracing for these trees.…”
Section: Discussionmentioning
confidence: 99%